A method of primary microsurgical debridement of lacrimal canaliculus ruptures in eyelid injuries (Ukrainian Journal of Ophthalmology, 2026)
Background. Eyelid injuries with the rupture of lacrimal canaliculi are most common for injuries to the lacrimal drainage system and make up approximately 47-48 % of all eyelid injuries. In the absence of correctly-performed primary microsurgical debridement (PMCD) of such injuries there can be formed coloboma and deformation of the eyelid, irreversible strictures and obliteration of canaliculi. Permanent unbearable tears, sour eyes, and limitation of capability for work-related activity require performing reconstructive surgery. PMCD of fresh injuries is much more effective than reconstructive surgery in the period of scarring when it is difficult to find and suture ends of a disrupted canaliculus. Such patients make up a considerable part of incurable watery eye. That is why, the development of PMCD of the eyelid injuries with lacrimal canaliculus ruptures is of relevance.